Clinical and genetic characteristics of new allele variants of the Mowat–Wilson syndrome caused by ZEB2 gene mutations - I. A. Akimova; T. V. Markova; F. A. Konovalov; A. V. Antonets; E. L. Dadali (Нервно-мышечные болезни, 2018)
To date, a large number of monogenic diseases and syndromes, in the clinical picture of which there are convulsions, a psycho-speech development delay and dysmorphic features have been described. One of the hereditary syndromes with a specific phenotype is the Movat–Wilson syndrome. To diagnose the syndrome, a set of survey methods was used: genealogical analysis, neurological examination, evaluation of intellectual development with the help of psychological tests, and sequencing of the new generation exome. As a result of sequencing exome on the panel of genes responsible for the emergence of hereditary epilepsy, two patients of different sex at the age of 10 and 5 years were identified with previously not described mutations in the ZEB2 gene in the heterozygous state. Clinical manifestations of the disease in these patients were of varying degrees of severity, which can be explained in terms of the functional significance of the changes detected. The variety of clinical manifestations of the same disease leads to considerable difficulties in diagnosing, however, due to the introduction of the nextgeneration sequencing in medical practice, the effectiveness of diagnosing hereditary diseases and syndromes, the verification of which has been difficult for a long time, has increased significantly.